Ghost bird - Fuller, Lisa (University of Queensland Press, 2019)
Stacey and Laney are twins - mirror images of each other - and yet they're as different as the sun and the moon. Stacey works hard at school, determined to get out of their small town. Laney skips school and sneaks out of the house to meet her boyfriend. But when Laney disappears one night, Stacey can't believe she's just run off without telling her.